Cynipidae (Insecta: Hymenoptera) fauna of Kazdağı National Park (Turkey) - Karaca, Gamze; Katilmiş, Yusuf (Zootaxa, 2020)
Field surveys were carried out to determine the richness of the Cynipidae fauna of Kazdağı National Park, located on the border of Edremit county (Balıkesir province, Turkey). Gall samples of cynipids were collected or photographed on Quercus and Rosa host plants. As a result, 53 cynipid species belonging to 3 different tribes were found or observed in the surveyed area. 14 and 8 species were recorded as new for the Cynipidae fauna of Balıkesir and Çanakkale provinces respectively, including the first locality record of Andricus hystrix Trotter, 1897 for Turkey. In addition, color photos of reared cynipid wasps from their galls and the observed cynipid galls on their host plant species are presented.